Biodegradable silk catheters for the delivery of therapeutics across anatomical repair sites. Issue 3 (26th April 2018) - Brown, Joseph E.; Tozzi, Lorenzo; Schilling, Benjamin; Kelmendi‐Doko, Arta; Truong, April B.; Rodriguez, Maria J.; Gil, Eun Seok; Sucsy, Robert; Valentin, Jolene E.; Philips, Brian J.; Marra, Kacey G.; Rubin, J. Peter; et al.
Abstract: Biodegradable silk catheters for the delivery of therapeutics are designed with a focus on creating porous gradients that can direct the release of molecules away from the implantation site. Though suitable for a range of applications, these catheters are designed for drug delivery to transplanted adipose tissue in patients having undergone a fat grafting procedure. A common complication for fat grafts is the rapid reabsorption of large volume adipose transplants. In order to prolong volume retention, biodegradable catheters can be embedded into transplanted tissue to deliver nutrients, growth factors or therapeutics to improve adipocyte viability, proliferation, and ultimately extend volume retention. Two fabrication methods are developed: a silk gel‐spinning technique, which uses a novel flash‐freezing step to induce high porosity throughout the bulk of the tube, and a dip‐coating process using silk protein solutions doped with a water soluble porogen. Increased porosity aids in the diffusion of drug through the silk tube in a controllable way. Additionally, we interface the porous tubes with ALZET osmotic pumps for implantation into a subcutaneous nude mouse model. The work described herein will discuss the processing parameters as well as the interfacing between pump and cargo therapeutic and the resulting release profiles. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2018. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 501–510, 2019.